On the dissolution of sponge silica: Assessing variability and biogeochemical implications - Maldonado, Manuel; López-Acosta, María; Abalde, Samuel; Martos, Isabel; Ehrlich, Hermann; Leynaert, Aude (Frontiers in Marine Science, 2022)
The dissolution of the biogenic silica that constitutes the skeletons of silicifying organisms is an important mechanism for regenerating dissolved silicon in the ocean. The silica skeletons deposited to the seafloor after the organisms die keep dissolving until becoming definitively buried. The low dissolution rate of sponge skeletons compared to that of diatom skeletons favors their burial and makes sponges (Phylum Porifera) to function as important silicon sinks in the oceans. However, it remains poorly understood whether the large variety of siliceous skeletons existing in the Porifera involves similar variability in their dissolution rates, which would affect the general conceptualization of these organisms as silicon sinks. Herein we investigated kinetics of silica dissolution for major types of skeletons in the three siliceous lineages of Porifera, following standardized digestion conditions in 1% sodium carbonate with orbital agitation at 85°C. The results are compared with those of a previous study conducted under identical conditions, which considered diatom silica, sponge silica, and lithogenic silica. Unexpectedly, the silica of homoscleromorph sponges dissolved only a bit slower than that of freshly cultured diatoms and as fast as diatom earth. However, the rest of sponge skeletons were far more resistant, although with some differences: the isolated spicules of hexactinellid sponges dissolved slightly faster than when forming frameworks of fused spicules, being hexactinellid frameworks as resistant to dissolution as the silica of demosponges, irrespective of occurring in the form of isolated spicules or frameworks. The experiments also indicated that the complexation of sponge silica with aluminum and with chitin does not increase its resistance to dissolution. Because the rapidly-dissolving homoscleromorph sponges represent less than 1% of extant sponges, the sponge skeletons are still conceptualized as important silicon sinks due to their comparative resistance to dissolution. Yet, the turnover of silica into dissolved silicon will always be faster in environments dominated by hexactinellids with isolated spicules than in environments dominated by other hexactinellids and/or demosponges. We discuss whether the time required for a given silica type to completely dissolve in 1% sodium carbonate could be a predictor of its preservation ratio in marine sediments.